Folic Acid Alleviates High Glucose and Fat-Induced Pyroptosis via Inhibition of the Hippo Signal Pathway on H9C2 Cells - Hong, Lei; Zha, Yingjie; Wang, Chen; Qiao, Shigang; An, Jianzhong (Frontiers in Molecular Biosciences, 2021)
Diabetic cardiomyopathy (DCM) is the leading cause of death in diabetic patients. Folic acid has a protective effect on diabetes-induced cardiomyocyte damage. The aim of this study was to explore the effects of folic acid on cardiomyocytes cultured under high glucose and fat (HGF) conditions and type 2 diabetes mellitus (T2DM) mice, and elucidate the underlying mechanisms. Bioinformatics analysis was used to identify the key genes in T2DM, and the potential drugs were identified through the Drug-Gene Interaction Database. H9C2 cardiomyocytes were cultured with 30 mM glucose and 500 nM palmitic acid in the presence or absence of folic acid or YAP1 inhibitor (verteporfin). The cell viability and lactate dehydrogenase (LDH) release were measured using specific assay kits. Pyroptosis was detected by flow cytometry. The concentrations of IL-1β and IL-18 in the supernatants were measured by ELISA. The NLRP3, ASC and caspase-1 mRNA levels were detected by qRT-PCR and that the proteins expression of NLRP3, ASC, cleaved caspase-1 (p10), caspase-1, YAP1, p-YAP1, LATS1 and P-LATS1 were detected by Western blotting. C57BL/6 mice were fed with high fat diet combined with streptozotocin (STZ) intraperitoneally to establish a T2DM model, folic acid or PBS treatment for eight weeks by gavagation, blood glucose and body weight were measured every four weeks, mouse heart tissue was used to detect pyroptosis and hippo signaling pathway related protein expression. We identified 101 differentially expressed genes in the cardiac tissues of type 2 diabetes mellitus mice that were associated with membrane sodium ion transport, serine-type endopeptidase activity and renin-angiotensin system. The significant module genes in the protein-protein interaction networks were Ceacam1, Art4, Vnn1, Ntm and Folr2, and folic acid targeted the Folr2 gene. Folic acid alleviated HGF-induced cell damage in vitro and vivo by decreasing activation of the Hippo pathway, as indicated by lower LDH release and increased cell viability, and decreased expression of NLRP3, ASC, cleaved caspase-1, IL-1β, IL-18, p-YAP and p-LATS. Verteporfin neutralized the protective effect of folic acid by reversing YAP-induced pyroptosis. Folic acid reduced NLRP3 inflammasome-mediated pyroptosis by down-regulating the Hippo signaling pathway, thereby effectively reducing T2DM-induced damage in H9C2 cells and animals.